The concept of smart cities: a sustainability aspect for future urban development based on different cities - Addas, Abdullah (Frontiers in Environmental Science, 2023)
To meet the needs of residents, scientists have suggested the concept of smart cities for urban transformation. Urban green spaces (UGSs) are designed to improve lifestyles. Environmental performance on a global scale is becoming challenging due to climatic changes and rapid advancement. To remedy these issues, the establishment of highly sustainable and healthier ecosystems is a crucial demand, placing an emphasis on the design of smart cities to prevent disease and address the basics of living quality. Urban populations are increasing enormously, which is a strong obstacle to developing a pollution-free environment. This study examines the current developments of cities, especially the sustainability of smart cities, which is required to meet the current demands. In addition to the developments, the ranking of different cities is compared. To explain the climate-related goals, national and international objectives and the legal framework are considered. The study compares the cities of Vienna, Copenhagen, Amsterdam, and Hamburg. The comparison is based on four categories: land distribution and use; mobility and transport; building standards; and supply and disposal. Owing to the high standard of living and its leading position in various rankings, special attention is paid to Vienna. The work is well developed with various components of sustainability and future development to enhance the quality of life and minimize air pollution. Finally, the problems and improvement possibilities of the cities are discussed. The study aims to look at the sustainability goals and projects that could be important in an ecological and sustainable city in the future. The comparison study of different cities shows the importance of smart cities and their effect on health.